Stability Analysis of Wind Turbine Blades Based on Different Structural Models - Bin Wang; Ying Li; Shan Gao; Kanmin Shen; Shengxiao Zhao; Yu Yao; Zhilu Zhou; Zhenhong Hu; Xing Zheng (Journal of Marine Science and Engineering, 2023)
In order to better simulate the actual working conditions of wind turbines more realistically, this paper adopts the two-way fluid–structure coupling method to study the NREL 5 MW wind turbine, considering the blade coupling deformation and equivalent stress and strain distribution of the blades with different internal structures under different working conditions. The results show that the maximum equivalent stress and strain distribution of the beam–structure wind turbine blade was near the leading edge of the blade. The maximum equivalent stress and strain distribution of the shell structure wind turbine blade was near the leading edge of the blade root, and the dangerous area is obvious but smaller than that of the beam-type wind turbine. The coupled deformation of a wind turbine model with a shell structure blade with a web is significantly reduced, and the equivalent stress and strain distribution of the skin is similar to that of the shell structure, but the numerical value and the maximum equivalent stress distribution area are significantly smaller. From the comparison of the three, the shell structure blade with a web is the best.